Анатомічна будова та структура епідермісу видів роду Hemerocallis L. в умовах посушливого степу - Krokhmal, I.I.; Puhachova, A.Yu. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
Peculiarities of the leaf anatomical structure and the anatomical and morphological features of epidermis were studied of Hemerocallis L. species are detected. Their adaptive changes and ecological peculiarities under the dry steppe condiitons were revealed. The most tolerant species – Hemerocallis minor and H. citrina – were determined. It was found out that species of the genus Hemerocallis are characterized by appearance of the various anatomical adaptaton features to the rigid natural and climatic conditions of the region of introduction: apperance of stomas on the abaxial epidermis, thickening of the abaxial and adaxial epidermis, larger area of the ventilating tissue, greater stomatal density on the abaxial and adaxial epidermis, decrease of dimensions of stomatal and epidermial cells, appearance of the palisade mesophyll.